Inventarisasi Lumut Hati Bertalus Kompleks (Kelas Marchantiopsida) Di Taman Kota Pontianak - Mukarlina, Agus Paryono, Elvi Rusmiyanto Pancaning Wardoyo, (Universitas Tanjungpura, 2017)
This research aims to determine the species of complex thalloid livertwort in the Pontianak City Park. Sampling was conducted using the cruise method and was conducted from March to May 2016 in 13 locations of Pontianak city park namely Taman Tugu Khatulistiwa, Taman LAPAN, Taman Tol Kapuas 1, Taman Dinas PU Kota, Taman Jl. Ahmad Yani, Taman Akcaya, Taman Jl. Tengku Umar, Taman Jl. HOS Cokroaminoto, Taman Jl. Tanjungpura, Taman Alun-alun Kapuas, Taman Pancasila, and Taman Jl. Tebu. The research obtained four species of complex thalloid livertworts, namely Mannia sp., Marchantia paleacea, Riccia fluitans, and Riccia sorocarpa. M. paleacea is a rare species found only in one location of the park and R. fluitans is the species often found i.e. in the 10 locations of the park.